PERAN STRATEGIS INTELLECTUAL CAPITAL SEBAGAI VARIABEL ANTARA PENGARUH FINANCIAL CAPITAL TERHADAP KINERJA PERUSAHAAN - Moh. Nasih (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
According to the classical theory of the firm, a firm can create value and earn maximum profits through financial capital. This view is valid in a stable environment. In recent decades, environmental conditions getting really erratic. Therefore, the role of financial capital in creating value and profitability is questionable. According to the modern theory of enterprise, intellectual capital is more dominant than the financial capital. This study aimed to examine the relationship/influence of financial capital and intellectual capital, directly or indirectly, to the company's financial performance among banking companies in Indonesia. Data obtained from banks, which in a single entity. Data that qualify the requirements is processed by using Structural Equation Modeling (SEM). The analysis showed that the financial capital (assets) indirectly influential, positive, and has significant impact on the firm's financial performance through intellectual capital and non-financial performance. Indirect effect on the financial performance of assets through intellectual capital is estimated at 0.166 and through non-financial performance to financial performance estimated at 0,600 (ROA) and at 0.617 (NI). Thus it is true that intellectual capital is a strategic asset that mediates the creation of superior performance of banking companies in Indonesia.